Isolation of a Pseudomonas sp. Which Utilizes the Phosphonate Herbicide Glyphosate - Moore, J. Kent (1983)
A strain of bacteria has been isolated which rapidly and efficiently utilizes the herbicide glyphosate (N-phosphonomethylglycine) as its sole phosphorus source in a synthetic medium. The strain (PG2982) was isolated by subculturing Pseudomonas aeruginosa ATCC 9027 in a synthetic broth medium containing glyphosate as the sole phosphorus source. Strain PG2982 differs from the culture of P. aeruginosa in that it is nonflagellated, does not produce pyocyanin, and has an absolute requirement for thiamine. Strain PG2982 has been tentatively identified as a Pseudomonas sp. strain by its biochemical activities and moles percent guanine plus cytosine. Measurements of glyphosate with an amino acid analyzer show that glyphosate rapidly disappears from the medium during exponential growth of strain PG2982. In batch culture at 30°C, this isolate completely utilized 1.0 mM glyphosate in 96 h and yielded a cell density equal to that obtained with 1.0 mM phosphate as the phosphorus source. However, a longer lag phase and greater generation time were noted in the glyphosate-containing medium. Strain PG2982 can efficiently utilize glyphosate as an alternate phosphorus source.